2014
DOI: 10.1144/sp401.16
|View full text |Cite
|
Sign up to set email alerts
|

Lateral ramps and strike-slip kinematics on Mercury

Abstract: At a global scale, Mercury is dominated by contractional features manifested as lobate\ud scarps, wrinkle ridges and high-relief ridges. Here, we show that some of these features are associated\ud with strike-slip kinematic indicators, which we identified using flyby and orbital Mercury Dual\ud Imaging System (MDIS) data and digital terrain models. We recognize oblique-shear kinematics\ud along lobate scarps and high-relief ridges by means of (1) map geometries of fault patterns\ud (frontal thrusts bordered by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…On Mercury strike-slip kinematics is always associated with some compressional deformation leading to transpressional structures (Massironi et al 2014). These structures often represent oblique and lateral ramps of frontal thrusts (Rothery and Massironi 2010, Massironi et al 2014.…”
Section: Origin Of Termmentioning
confidence: 99%
See 1 more Smart Citation
“…On Mercury strike-slip kinematics is always associated with some compressional deformation leading to transpressional structures (Massironi et al 2014). These structures often represent oblique and lateral ramps of frontal thrusts (Rothery and Massironi 2010, Massironi et al 2014.…”
Section: Origin Of Termmentioning
confidence: 99%
“…These structures often represent oblique and lateral ramps of frontal thrusts (Rothery and Massironi 2010, Massironi et al 2014. Their presence could be indicative of mantle convection and/or tidal despinning acting as a major geodynamic processes together with the dominant cooling and contraction of the planet.…”
Section: Origin Of Termmentioning
confidence: 99%
“…Their models provide renewed insights into how subsurface magma reservoirs inflate and rupture, and how these processes relate to volcano growth, caldera formation, and the associated emplacement of circumferential and radial dykes. Lateral ramps and strike-slip kinematics on Mercury Massironi et al (2014) investigate contractional features on Mercury for evidence of strike-slip deformation. Such evidence includes en echelon fold arrays, restraining bends, positive flower structures, stike-slip duplexes and crater rims that have been displaced by lobate scarps and high-relief ridges.…”
Section: R C Ghail and L Wilsonmentioning
confidence: 99%
“…The systematic orientation of structures in some areas of the planet (Melosh & McKinnon, ; Watters et al, ) strengthened the idea that, besides global contraction, a tidal despinning process influenced Mercury's tectonics in the past (Melosh & Dzurisin, ; Pechmann & Melosh, ). However, model predictions indicate that tidal despinning alone would have created a globally recognizable pattern of thrusts, strike‐slip, and normal faults (Beuthe, ; Melosh, ), whereas tectonics governed solely by global contraction should have caused isotropic stresses and a random orientation distribution of thrust faults (e.g., Klimczak et al, ; Massironi, di Achille, et al, ). Since this is not observed at a global scale, it has been suggested that despinning acted concurrently with global contraction during the early evolution of Mercury (e.g., Klimczak et al, ; Matsuyama and Nimmo, ), with some global contraction reworking inherited despinning faults (Dombard & Hauck, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent thermal models do not exclude this scenario, albeit it is more likely that the mantle is currently in a conductive state (Michel et al, ; Tosi et al, ). The occurrence of fold‐and‐thrust systems where extensive thrusts are bounded by lateral ramps that indicate a constant vergence has been suggested to be one surface evidence for the contribution of mantle convection to the total shortening (Massironi, di Achille, et al, ).…”
Section: Introductionmentioning
confidence: 99%